PEMANFAATAN ENTERPRISE ARCHITECTURE PLANNING PADA AKPER HARUM JAKARTA - Bastari, Johan (LPPM Universitas Nusa Mandiri, 2013)
Information system development aims to achieve the mission of information system in order to provide quality of data/information for the sake of business. The first step of achieving the mission of this information system is to plan the information system to identify information needs and possible innovations in the use of technology to improve enterprise performance. Planning can use Enterprise Architecture Planning (EAP) methodology which result blueprint of the architecture data, application architecture, technology architecture and implementation plan for the enterprise. In these cases, a study case for the planning of integrated information system development using EAP with applying value chain model and analysis approaches and tools is performed on AKPER Harum Jakarta. The result in this cases study is the enterprise model, information resource catalog documentation, data architecture, application architecture, technology architecture, and implementation plans. Result also provide a foundation for overcoming separate of a legacy system, of data integration, and lack of support from information system for the business functions.